Mixed Methods in Analysis of Aggressiveness and Attractiveness: Understanding PE Class Social Networks with Content Analysis - Maria Litsa; Alexandra Bekiari (MDPI AG, 2022)
The aim of this study is to detect and analyze the relationship between verbal aggressiveness and interpersonal attractiveness using four secondary-school PE classes in central Greece (88 nodes). Content analysis of open-ended questions, social network analysis, Spearman test and PCA have been implemented. Main results: scientific and social attractiveness are interrelated with a subsequent emergence of power structures and negatively related to verbal aggressiveness. Targets of verbal aggressiveness receive aggressiveness consisting of hurt, irony, rudeness and threat. The general grade and students' tendency for distinction are positively related to attractiveness and negatively related to verbal aggressiveness. Types of targets of interpersonal attractiveness are proposed ("the untargeted powerful" and "the targeted powerful").